1999
DOI: 10.1097/00005537-199901000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase activity in human squamous cell carcinoma of the head and neck

Abstract: These data suggest that tumor growth and malignancy is associated with a change in the enzymatic source of NO from calcium-independent NOS to calcium-dependent NOS isoform in primary localization. These data suggest that the inhibition of calcium-independent NOS activity in early stages and/or inhibition of calcium-dependent NOS activity in later stages could delay growth of solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 18 publications
6
28
0
Order By: Relevance
“…6 In this respect the high NOS2 expression of severe dysplasia noted in our study suggests that this process begins to occur before the transformation into invasive cancer.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…6 In this respect the high NOS2 expression of severe dysplasia noted in our study suggests that this process begins to occur before the transformation into invasive cancer.…”
Section: Discussionmentioning
confidence: 52%
“…[5][6][7] These studies demonstrated significantly increased expression and activity of NOS2 in tumor tissue. Enhanced angiogenesis also correlated with NO production both in resected tumor specimens and in an animal model, the rabbit cornea.…”
mentioning
confidence: 82%
“…As indicated in our prior works, a number of tumor cell lines have been adapted to HNO concentration levels including those from lung [11,[46][47][48], head and neck [3,[49][50][51][52], and breast [7], suggesting that NO adaptation is also a universal property. In an attempt to further elucidate the impact of extended exposure from NO on underlying biological systems, we herein characterize the four newly The ten most up-regulated appear first and the ten most down-regulated appear below within each cell line type NA not available a Gene symbols used vary according to the supplier of the gene chip created breast adenocarcinoma HNO cell lines [7], along with each respective parent cell line.…”
Section: Resultsmentioning
confidence: 85%
“…NO is termed as a ‘double-edged sword’ as it possesses both beneficial and deleterious effects depending on the amounts and conditions under which it is produced [54]. However, high NO production is required in the early stage of head and neck carcinoma, leading to iNOS expression in order to activate angiogenesis [55]and enhance tumor cell adhesivity and permeability [56]. Thus, a new cancer therapy by preventing angiogenesis, invasion, and metastasis through inhibition of NOS generation is proposed [34]and experimental drugs for specific iNOS inhibitors, such as 1400W [57], have been developed.…”
Section: Discussionmentioning
confidence: 99%